Evaluation of different respiratory samples and saliva for the detection of SARS CoV-2 RNA - KARAHASAN, AYŞEGÜL; ERTÜRK ŞENGEL, BUKET; GÜNEŞER, DENİZ; KORTEN, VOLKAN (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: We aimed to analyse the positivity rate and cycle threshold values indicating viral loads for SARS CoV-2 among different respiratory specimens and also to evaluate the diagnostic efficacy of saliva samples. Materials and Methods: We included combined oropharyngeal and nasopharyngeal swab (cONS), sputum, and tracheal aspirate (TA) specimens of patients. Unpreserved saliva samples were collected prospectively from hospitalized patients within 72 hours of admission. SARS CoV-2 RNA was extracted by using Bio-Speedy viral nucleic acid buffer than RT-PCR was performed with Bio-Speedy COVID-19 qPCR detection kit. Results: Retrospective evaluation revealed SARS CoV-2 RNA in 19.66% of cONS (n: 5819), 30.77% of sputum (n: 39), 29.41% of TA samples (n: 34) from 4812 patients. In the majority (86.72%) of the samples, the first cONS sample was positive. Consecutive cONS and sputum/TA samples were investigated in 52 patients of whom 11 were positive with either of these samples. Saliva positivity was detected in 60% of cONS positive (n: 20) and 30% of cONS negative (n: 12) patients. Conclusion: Although, cONS samples show the greatest diagnostic guidance, repeated sampling from multiple sites of the respiratory tract increases the possibility of COVID-19 diagnosis. Saliva samples might be considered as an alternative specimen.
Keywords: SARS Co V-2; COVID-19; RT-PCR; Upper respiratory samples; Saliva; Cycle threshold